DAMPAK EL NINO TERHADAP PRODUKSI DAN PENDAPATAN AGROINDUSTRI BERBASIS SINGKONG DI DESA KARANG ANYAR KECAMATAN GEDONGTATAAN KABUPATEN PESAWARAN - Cherli Medika; Zainal Abidin; Eka Kasymir (Lampung University, 2016)
This study aims to study the impact of El Nino on the production and revenues of cassava based on agroindustry in Karang Anyar Village, Gedongtataan Sub-district of Pesawaran District. The location was chosen purposively. The sample size was 37 kelanting industries and 13 cassava chips industries. The data of this research were collected from February to March 2016. The data was analyzed by income analysis and income statement analysis in addition to the middle test value. The study showed that there was significant difference on average production of cassava based on agroindustry between normal and El Nino seasons. There was also significant different on average income of cassava based on agroindustry between normal and El Nino season. There was significant difference on average total cost of cassava based on agroindustry between normal and El Nino seasons and there was significant difference on input and output prices of cassava based on agroindustry between normal and El Nino season. Key words: agroindustry, cassava, El Nino, impact